Odpowiedzi

  • Użytkownik Zadane
2010-04-13T16:43:37+02:00
A)12x-11(4x-3)+10(8-5x)+8(8x-13)=0
12x-44x+33+80-50x+64x-104=0
12x-44x-50x+64x=104-33-80
-18x=-9
x=0,5
spr: 12*0,5-11(4*0,5-3)+10(8-5*0,5)+8(8*0,5-13)=0
6+11+55-72=0
72-72=0
0=0
L=P

b) 4y -3=5(2y-9)
4y-3=10y-45
4y-10y=-45+3
-6y=-42
y=7
spr:4*7-3=5(2*7-9)
28-3=70-45
25=25
L=P

c)4,2(0,8y-1,4)=3,1(0,4y-1,76)
3,36y-5,88=1,24y-5,456
3,36y-1,24y=-5,456+5,88
2,12y=0,424
y=0,2
spr:4,2(0,8*0,2-1,4)=3,1(0,4*0,2-1,76)
-5,208=-5,208
L=P

2010-04-13T16:56:30+02:00
A) 12x-11(4x-3)+10(8-5x)+8(8x-13)=0
12x-44x+33+80-50x+64x-104=0
12x-44x-50x+64x=-33-80+104
-18x=-9/:(-18)
x=0,5
spr.: 12*0,5-11(4*0,5-3)+10(8-5*0,5)+8(8*0,5-13)=0
6-11(2-3)+10(8-2,5)+8(4-13)=0
6-22+33+80-25+32-104=0
0=0

b) 4y -3=5(2y-9)
4y-3=10y-45
-3+45=10y-4y
42=6y/:6
y=7
spr.:4*7-3=5(2*7-9)
28-3=5(14-9)
28-3=70-45
25=25

c) 4,2(0,8y-1,4)=3,1(0,4y-1,76)
3,36y-5,88=1,24y-5,456
3,36y-1,24y=5,88-5,456
2,12y=0,424/:2,12
y=0,2
spr.:4,2(0,8*0,2-1,4)=3,1(0,4*0,2-1,76)
4,2(0,16-1,4)=3,1(0,08-1,76)
0,672-5,88=0,248-5,456
-5,208=-5,208